Pengaruh Akuntabilitas Dan Transparansi Terhadap Kepercayaan Wajib Pajak Dalam Pemungutan Ppn (Survey Pada Dinas Pu Bina Marga Dan Tata Ruang Provinsi Sumatera Selatan) - rezaziu, M. Reza Eka Putra; Leriza Desitama Anggraini; Vhika Meiriasari (Universitas Indo Global Mandiri, 2024)
This research aims to determine and test the influence of accountability and transparency on taxpayers' trust in VAT collection at the Public Works Department of Highways and Spatial Planning, South Sumatra Province. The research methods used were to study a specific population or sample and to collect data and to analyse quantitative data. The target population studied was 40 partners of the Public Works Department of Highways and Spatial Planning of South Sumatra Province. The sampling technique that was used was non-probability sampling. This research was analyzed using SPSS, which aims to examine the influence of accountable and transparent on taxpayers' trust in VAT collection at the Public Works Department of Highways and Spatial Planning of South Sumatra Province. The results of this research show that the accountability variable (X1) partially has a positive and significant effect on taxpayer trust (Y), so H1 is accepted from the calculated t results to be greater than tTable, namely 4,620 > 1,996 and the significance value (Sig.) is 0.000 < 0.05. Then, the results of the transparency test (X2) partially have a significant effect on taxpayer confidence (Y), so H2 is accepted because tcount is greater than ttable, namely 4,314 > 1,996 and the significance value (Sig.) is 0.000 < 0.05. The results of the F test show that Fcount is greater than Ftable, namely 226,864 > 3.13 and a significant value of 0.000 < 0.05, so it can be concluded that accountability (X1) and transparency (X2) simultaneously have a significant influence on tax compliance (Y), so H3 is accepted. Keywords: Accountability, Transparency, Taxpayer Trust